Bio-synthesized silver nanoparticles using Zingiber officinale rhizome extract as efficient catalyst for the degradation of environmental pollutants. Issue 2 (1st February 2020) - Barman, Kailash; Chowdhury, Devasish; Baruah, Pranjal K.
Abstract: Silver nanoparticles were synthesized through an eco-friendly process using an extract of Zingiber officinale rhizome. Spectrophotometric analysis of the AgNPs exhibited sharp band centered around 400–420 nm. The functionality of phytochemicals present in the Z. officinale was identified using FTIR spectroscopy. The characterization of synthesized AgNPs was done by UV-Vis spectroscopy, transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), and selected area electron diffraction pattern (SAED), particle size, and zeta potential analyzer. The average measured size and diameter of AgNPs were ∼20 nm, measured by XRD and TEM. We have successfully utilized the AgNPs as efficient catalyst in degradation of harmful dyes: methylene blue, methyl red, and safranin O. The rate constant for the degradation of dyes was found to be 14.25 × 10 −3 sec −1, 9.68 × 10 −3 sec −1 and 4.72 × 10 −3 sec −1 for methylene blue, methyl red, and safranin O respectively.